Mapping the Landscape of Sustainability Reporting: A Bibliometric Analysis - Singh, Shahni; Dutta, Sudeshna; Sharma, Debabrata (Prabandhan: Indian Journal of Management, 2024)
Purpose : The purpose of this research was to identify, map, and evaluate the body of literature on sustainability reporting. The study aimed to enhance understanding of research trends and gaps in this field. Design/Methodology/Approach : The study utilized a bibliometric analysis approach to explore scholarly publications cataloged in the Scopus database. The analysis was conducted using VOSviewer software to uncover dominant themes, influential authors, key sources, highly cited articles, and leading countries in the domain of SR. The keyword “sustainability reporting” was employed to ensure the relevance of the findings. Findings : The research revealed significant insights into publication patterns, notable articles, and prominent authors within the field of SR. It identified key trends, influential contributions, and gaps in the existing literature. Practical Implications : The findings provided a thorough understanding of SR practices, which was beneficial for all stakeholders, including consumers, investors, and industries. The study’s findings could help stakeholders make wise choices and improve their understanding of SR practices and trends. Originality/Value : The study filled up existing gaps and provided a thorough mapping of the research environment, which added to the body of knowledge on sustainability reporting. What makes it unique is the thorough bibliometric analysis that gives a thorough summary of the field and identifies areas that require more research.